Clinal variation or validation of a subspecies? A case study of the Graptemys nigrinoda complex (Testudines: Emydidae). (12th March 2014) - Ennen, Joshua R.; Kalis, Marley E.; Patterson, Adam L.; Kreiser, Brian R.; Lovich, Jeffrey E.; Godwin, James; Qualls, Carl P.
<x xml:space="preserve">Abstract</x> Widely distributed species often display intraspecific morphological variation due to the abiotic and biotic gradients experienced across their ranges. Historically, in many vertebrate taxa, such as birds and reptiles, these morphological differences within a species were used to delimit subspecies. Graptemys nigrinoda is an aquatic turtle species endemic to the Mobile Bay Basin. Colour pattern and morphological variability were used to describe a subspecies (G. n. delticola) from the lower reaches of the system, although it and the nominate subspecies also reportedly intergrade over a large portion of the range. Other researchers have suggested that these morphological differences merely reflect clinal variation. Our molecular data (mtDNA) did not support the existence of the subspecies, as the haplotypes were differentiated by only a few base pairs and one haplotype was shared between the putative subspecies. While there were significant morphological and pattern differences among putative specimens of G. n. nigrinoda, G. n. delticola and G. n. nigrinoda × delticola, these differences probably represent clinal variation as they were also related to environmental variables [i.e. cumulative drainage area and drainage (categorical)]. Specimens occupying slow‐current, high‐turbidity river reaches (e.g. the Tensaw River) exhibited greater relative carapace heights and more dark pigmentation, while specimens occupying fast‐current, clearer rivers (e.g. the upper Alabama, Cahaba and Tallapoosa rivers) exhibited lower carapace heights and more yellow pigmentation. Given the absence of clear molecular and morphological differences that are related to drainage characteristics, we suggest that there is not sufficient evidence for the recognition of G. n. delticola as a distinct subspecies. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 111, 810–822.